Modelling, Simulation and Experimental Verification of a 3 DOF Moving Platform with Parallel Kinematics and Electro-Hydraulic Proportional / Servo Control System - Ezz Eldin Ibrahim; Ahmed Azouz; Tarek Elnady; Mohamed Saffaa Hassan; Ibrahim Saleh (Communications)
Hydraulic motion platforms are widely utilized in various environments due to their capacity to bear heavy loads and provide long actuator strokes. The predominant control system employed for hydraulic motion platforms is the electro-hydraulic servo system (EHSS) due to its high accuracy and robustness. However, compared to other types of hydraulic valves, the electro-hydraulic servo valve (EHSV) is less durable. An alternative system to EHSS is the electro-hydraulic proportional system (EHPS), which employs an electro-hydraulic proportional valve (EHPV) instead of the EHSV. The EHPV resolves the durability issue at the expense of accuracy and system error. The optimization of durability and accuracy is the core of this study. The tracking behavior and response of both Three degrees of freedom (3 DOF) motion platforms using EHSS and EHPS are investigated across different frequency ranges.